Development of an alternative uniform design for the Metro Aides, Angela L. Marbil; Angelita M. Dizon, adviser. - Marbil, Angela L.; Dizon, Angelita M. (1994.)
Reviewing the design details of the current uniform of the Metro Manila Aides is what the study is all about. Researched works, critical observations and interviews were used to come up with a new deign. Fifty questionnaires were also given out for additional information. Based on the gathered data, it was found that there are, indeed, problems in the current dress code. The use of Jones's technique of visual inconsistencies aided the researcher in designing this study. Inconsistencies in style to image, sizing to fit, and fabric performance to aesthetics were some of the problems revealed in the study. A design criteria together with interviews and review of related literature, a new design was implemented. The changes made in the uniform were focused on the specific tasks and needs of the street sweepers. The prototype includes a shirt with a raglan sleeves, a pair of gloves and a nose covering. The buri hat is retained while the pants can be of any jeans. The prototype was presented and met with great enthusiasm. It was worn by one Metro Aide to test for fit and comfort and found acceptable in terms of ease in dressing and comfort in wearing. Thus, the alternative new design is more helpful to street sweepers.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Street cleaners -- Clothing; Fashion design